2014
DOI: 10.7600/jspfsm.63.223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitual exercise and diet restriction on the hepatic fat accumulation in Zucker fatty rats

Abstract: We investigated the effects of habitual exercise and diet restriction on the hepatic fat accumulation in Zucker fatty rats. Male 6-week-old Zucker fatty rats were divided into obese (Ob), diet restriction (DR), and diet restriction + exercise (DR + Ex) groups. Male Zucker lean rats (L) were used as a control group. The rats in the L and Ob groups were maintained on ad libitum diets. The rats in the DR and DR + Ex groups were fed a 30% restricted diet. The rats in the DR + Ex group exercised voluntarily on a wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Many studies have reported that skeletal muscle loss and fatty liver are closely related and that hepatic fat accumulation increases in sarcopenia patients and sedentary subjects [ 10 , 11 , 12 ]. We recently characterized the effects of habitual exercise and/or diet restriction on hepatic fat accumulation in Zucker fatty (ZF) rats [ 13 , 14 ]. ZF rats have a mutation in the leptin receptor gene that causes increased appetite and weight gain [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that skeletal muscle loss and fatty liver are closely related and that hepatic fat accumulation increases in sarcopenia patients and sedentary subjects [ 10 , 11 , 12 ]. We recently characterized the effects of habitual exercise and/or diet restriction on hepatic fat accumulation in Zucker fatty (ZF) rats [ 13 , 14 ]. ZF rats have a mutation in the leptin receptor gene that causes increased appetite and weight gain [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we found that dietary restriction in ZF rats did not ameliorate the development of fatty liver but rather accelerated it. We also found that the same dietary restriction combined with physical exercise prevented intrahepatic fat accumulation and maintained a healthy liver [ 13 ]. Moreover, in previous studies focusing on fat cell size, it was shown that a combination of exercise and dietary restriction in ZF rats suppresses fat cell size hypertrophy and prevents fatty liver [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, few reports have examined these effects simultaneously. We recently characterized the effects of habitual exercise and/or diet restriction on hepatic fat accumulation in Zucker fatty (ZF) rats [ 10 ]. Histologically, the intrahepatic accumulation of triglycerides (TGs) was suppressed by habitual exercise, but not by dietary restriction alone [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently characterized the effects of habitual exercise and/or diet restriction on hepatic fat accumulation in Zucker fatty (ZF) rats [ 10 ]. Histologically, the intrahepatic accumulation of triglycerides (TGs) was suppressed by habitual exercise, but not by dietary restriction alone [ 10 ]. ZF rats have a mutation in the leptin receptor gene that causes increased appetite and weight gain; thus, they are used as an animal model of obesity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…They show low physical activity levels compared with ordinary rats and eventually develop fatty liver 17) . Kurosaka et al 18) found that dietary restriction in ZF rats did not ameliorate the development of fatty liver, but accelerated it. They also found that the same dietary restriction combined with physical exercise prevented intrahepatic fat accumulation and maintained a healthy liver.…”
Section: Differential Effects Of Dietary Condition and Physical Activitymentioning
confidence: 99%